Expression of GLUT1 in Pseudopalisaded and Perivascular Tumor Cells Is an Independent Prognostic Factor for Patients With Glioblastomas. Issue 5 (14th December 2018) - Komaki, Satoru; Sugita, Yasuo; Furuta, Takuya; Yamada, Kyohei; Moritsubo, Mayuko; Abe, Hideyuki; Akiba, Jun; Miyagi, Naohisa; Nakamura, Hideo; Miyoshi, Hiroaki; Ohshima, Koichi; Morioka, Motohiro
Abstract: Glioblastomas are highly aggressive brain tumors with a particularly poor prognosis. Glucose transporter-1 (GLUT1/SLC2A1), a uniporter that is expressed by various carcinomas and may be involved in malignant neoplasm glycometabolism, may also be related to prognosis in glioblastomas. GLUT1 is essential to central nervous system glycometabolism. To clarify the exact role of GLUT1 in glioblastoma, we assessed the expression and localization of GLUT1 in patient samples by immunohistochemistry and in situ RNA hybridization. This revealed that GLUT1 was mainly expressed on perivascular and pseudopalisaded tumor cell membranes. All samples expressed GLUT1 to some degree, with 30.8% showing stronger staining. On the basis of these data, samples were divided into high and low expression groups, although SLC2A1 mRNA expression was also higher in the high GLUT1 expression group. Kaplan-Meier survival curves revealed that high GLUT1 expression associated with lower overall survival (log-rank test, p = 0.001) and worse patient prognoses (p = 0.001). Finally, MIB-1 staining was stronger in high GLUT1 expression samples (p = 0.0004), suggesting a link with proliferation. We therefore hypothesize that GLUT1 expression in glioblastomas may enhance glycolysis, affecting patient prognosis. Examination of GLUT1 in patients with glioblastomas may provide a new prognostic tool to improve outcome.